Dreams of gods & monsters - Taylor, Laini (Taylor, Laini. Daughter of smoke & bone trilogy, 2014)
From the streets of Rome to the caves of the Kirin and beyond, humans, chimaera, and seraphim will fight, strive, love, and die in an epic theater that transcends good and evil, right and wrong, friend and enemy.